Design, dynamic simulation, and optimal size selection of a hybrid solar/wind and battery-based system for off-grid energy supply. (March 2022) - Cao, Yan; Taslimi, Melika S.; Dastjerdi, Sajad Maleki; Ahmadi, Pouria; Ashjaee, Mehdi
Abstract: Remote energy systems are applicable, especially in critical circumstances like earthquakes, floods, etc. Besides, renewable energy systems are suitable energy sources in remote areas. Therefore, Due to high solar and wind potential and its location as an earthquake-prone, a solar-wind energy system for a remote application on a Conex is presented in this study. Considered wind turbines have power production of 1 kW and 3 kW. PV panels have an efficiency of about 20%. This Conex has 12 m 2 of the area and resides three to five people and supplies 520 W power consumption of equipment except for the HVAC unit. A considered lifetime of the Conex is 20 years. The considered capacity of batteries is about 100–200 Ah. Six cities are selected as representatives of the six major climate types in Iran. The studied system is optimized for each city. The heating and cooling demand of Conex in cities are specified using TRNSYS software. The heat pump's electricity requirement as a cooling and heating unit with COP of four, lighting (20 W), laptops (140 W), and refrigerators (360 W) is calculated for Conex in each city. Mixed-integer linear programming is employed to optimize an off-grid renewable energy system to supply this electricity demand. The system's total cost, which includes the initial and O&M cost of PV panels and wind turbines, and the capital and replacement cost of the batteries together with the loss of power supply probability during a year, are considered two objective functions. The interest rate is assumed to be 15%. Achieved results show that Iran's solar and wind potential can balance the required load of the Conex with a probability of power outage as low as 1% of a year. However, there is a variance in the cost of the required renewable energy system for supplying Conex power consumption for different climate zones: in the Mediterranean region, the system costs 500–5000 $ as the most expensive one, and in the hot coastal dry region, it costs 900 $-2000 $ as the most cost-efficient region. Finally, results show that wind turbines can be cost-effective energy suppliers for most considered climates, especially considering O&M costs. This study can fill the gap of requiring off-grid temporary portable residences in different climates after disasters, which destroy buildings. Therefore, the lack of these temporary residences can be supplied without adding greenhouse gases to the environment, which reduces greenhouse emissions and electrical grid dependence of the building sector. Highlights: A solar-wind energy system for an off-grid residential Conex is presented. Proposal of a new off-grid system for location with high risk of an earthquake. Six critical cities are selected as major climates in Iran. A mixed-integer linear program determining the optimum system is implemented. Optimization results are brought using pareto frontiers.